PENGARUH JUMLAH RUAS SETEK DAN DOSIS UREA TERHADAP PERTUMBUHAN SETEK PUCUK NILAM (Pogostemon cablin Benth.) - Erida Nurahmi; Kamarlis Karim; Tarmizi Tarmizi (Jurnal Floratek, 2013)
The objectives of this research were to study effects of cutting internode numbers and urea dosages, and interaction between them on pogostemon bud cutting growth. This research was done at Kajhu Village, Baitussalam Sub District, Aceh Besar District, Aceh Province, from February 15th to April 15th 2011. Experiment was arranged according to Factorial Randomized Complete Block Design 3 x 3, with 3 replicates. Each of replications was consisted of 3 plants, resulting 81 experimental units. The first factor was cutting internode numbers, consisted of 3 levels, i.e. 2, 3 and 4 internodes. The second factor was urea dosage, also consisted of 3 levels, i.e. 1, 2 and 3 g urea/cutting. All cuttings were planted in polybags; one cutting per polybag, filled with 5 kg of soil, with one internode was inserted into the soil. The result showed that there were highly significant interactions between cutting internode numbers and urea dosages on pogostemon cutting leaves and bud numbers at 60 days after planting, which means that cuttings with different internode numbers responded differently to urea dosage increases. The best one was cutting with 4 internode numbers and the best urea dosage was 2 g/cutting.  The best combination was cutting with 2 internodes and 2 g urea/cutting.